Delineating surface and sub surface waterlogged area using RS & GIS: a case study of Rachna Doab - Mehmood, Hannan; khan, Mobushir Riaz; Amin, Muhammad; Ali, Rizwan (International Journal of Advanced Geosciences, 2017)
Remote sensing (RS) combined with Geographical Information Systems (GIS) offers fabulous contrasting option to routine mapping strategies in observing and mapping of surface and sub-surface waterlogged areas. In the present study, a pre-monsoon and post-monsoon surface waterlogged area was delineated in the four districts of Rachna doab, using Landsat 8 data acquired for the year 2014. Modified Normalized Difference Water Index (MNDWI) was used mainly to delineate surface waterlogged areas. Perennial surface waterlogged areas were assessed for the study area by incorporating the waterlogged areas derived for both the pre-monsoon and post-monsoon seasons under GIS environment. Result shows that the total surface waterlogged area in pre-monsoon is 5,861 ha, which is 0.51 % of study area and for post-monsoon the surface waterlogging is 8,661 ha, which is 0.75% of study area respectively. Perennial surface waterlogging is 3,573 ha, which is 0.30% of the study area. Maximum waterlogged area was observed in Gujranwala district followed by Hafizabad, Sheikhupura and Nankana Sahib respectively. Further, waterlogged areas caused by rise in groundwater level were also assessed spatially under ArcGIS environment using the piezometric data pertaining of pre-monsoon and post-monsoon seasons for the year 2014 which were spread all over the study area. The analysis of both the seasons of groundwater levels indicates that the area under critical category during pre-monsoon period was 47,309 ha, which is 4% of the total area. Area under most critical category during post-monsoon period increased from 47,309 to 131,070 ha, which is 11% of the total. The study shows utility of remote sensing and GIS for evaluation of waterlogging areas especially where waterlogging situations occurs because of excessive irrigation and accumulation of rain and floodwater.